Innovation Approaches to Inclusive Education in Europe – The Impact of Second Chance Schools - Blagoeva, Elena (English Studies at NBU, 2024)
This article presents research and findings related to the Second Chance Schools - an innovative approach which is gaining strength and popularity in recent years but is almost unknown in Bulgaria. The documentary research, the analysis of interviews of the various actors and the online surveys during the project revealed a set of characteristics of Second Chance Schools common to most countries in Europe. The study reveals that in the countries where the SCS approach has been applied, early school leavers’ rates are going down.